Pengaruh Media Pembelajaran dan Literasi Digital Terhadap Hasil Belajar PAI Siswa SMP Negeri 10 Purworejo - Khasanah, Kun Fasikhatul; Eliyanto, Eliyanto (Tarbi: Jurnal Ilmiah Mahasiswa, 2025)
The objectives of the study are: (1) to determine the effect of learning media on the PAI learning outcomes of students at SMP Negeri 10 Purworejo. (2) to determine the effect of digital literacy on the PAI learning outcomes of students at SMP Negeri 10 Purworejo. (3) to determine the effect of learning media and digital literacy together on the PAI learning outcomes of students at SMP Negeri 10 Purworejo. This study uses a correlational quantitative research approach. This study consists of two independent variables, namely learning media (X1), digital literacy (X2), and one dependent variable, namely students' PAI learning outcomes (Y). The data collection technique uses a questionnaire instrument. The research population was 253 students, while the research sample was 146 students. Before conducting the hypothesis test using simple regression and multiple regression, the validity and reliability of the instrument were tested and the analysis requirements were tested, including data normality and data linearity tests. Based on the research results, it can be concluded that: (1) Learning Media has a significant effect on the PAI Learning Outcomes of Students of SMP Negeri 10 Purworejo, as evidenced by the Sig value = 0.000 < α = 0.050, and the correlation coefficient value (r2) = 0.396 or contributes 39.6%. (2) Digital Literacy has a significant effect on the PAI Learning Outcomes of Students of SMP Negeri 10 Purworejo, as evidenced by the Sig value = 0.000 < α = 0.050, and the correlation coefficient value (r2) = 0.424 or only contributes 42.4%. (3) Learning Media and Digital Literacy together have a significant effect on the PAI Learning Outcomes of Students of SMP Negeri 10 Purworejo, as evidenced by the Sig value = 0.000 < α = 0.050, and the correlation coefficient value (R2) = 0.475 or contributes 47.5%.